The ministers' war : John W. Mears, the Oneida Community, and the crusade for public morality - Doyle, Michael, 1956- (Syracuse University Press, 2018)
Unbridled passions threatened nineteenth-century America, a vulnerable young nation already feeling beset by foreigners, corruption, and disease. Purifying crusaders like Hamilton College philosophy professor and Presbyterian minister John W. Mears mobilized to fight every sin and carnal lure, from liquor to free love. In Upstate New York's famed Oneida Community, Mears encountered his stiffest challenge. Oneida's founder and patriarch, John Humphrey Noyes, oversaw a radical Christian commune where men and women sexually mingled through the practice of "complex marriage." While others struggled to dislodge the community that had evolved since 1848 into a successful business venture and congenial neighbor, it was Mears who, after years of trying, rallied New York's church and university leaders for a final, concerted anti-Oneida campaign.In The Ministers' War, Doyle traces the full story of Mears and the crusade against the Oneida Community. He explores the ways in which Mears's multipurpose zeal reflected the passions behind the nineteenth-century temperance movement, the fight against obscenity, and the public animus toward unconventional thought. As an author, political candidate, and controversialist, Mears was a prominent moralizer at a time when public morality seemed to be most at risk.